كفاءة التدفقات النقدية التشغيلية و أثرها على ربحية و سيولة المؤسسة الاقتصادية دراسة حالة مطاحن بلغيث الكبرى بمداوروش ولاية سوق أهراس - - رحمة عتارسية; كريمة بوحجر (My University, 2021)
Thisstudy aims toevaluate the efficiency of operational cash flows in the economic institution and analyze its impact on profitability and liquidity in the major Balghith mills, using the ratios of liquidity andprofitability, as well as the ratios that link liquidity and profitability to operating cash flows, where the descriptive analytical approach was adopted in the context of analyzing the relationship The research variables and their projection on the institution under study with the use of its financial statements during the period (2010-2015), in addition to the statistical method and the case study on the applied side. The study concluded that measuring and evaluating the efficiency of operating cash flow management through efficiency indicators and its impact on liquidity and profitability ratios has a key role in revealing the strengths and weaknesses of the institution, and also helps in taking appropriate corrective measures to improve its efficiency and then raise its profitability and improve its liquidity.The fact that the success and continuity of economic institutions depends on the extent of their ability to achieve the highest profitability in a world where competition is fierce in parallel with setting an appropriate level of liquidity. The study also concluded that there is a statistically significant relationship between the efficiency of operational cash flow, liquidity and profitability of Balghith mills during the study period. .............................................................. تهدف هذه الدراسة إلى تقييم كفاءة التدفقات النقدية التشغيلية في المؤسسة الاقتصادية وتحليل أثرىا على الربحية والسيولة بمطاحن بلغيث الكبرى ، وذلك باستخدام نسب السيولة والربحية وكذلك النسب التي تربط السيولة والربحية بالتدفقات النقديةالتشغيلية، حيث تمّ الاعتماد على المنهج الوصفي التحليلي في سياق تحليل العلاقة بين متغيّّات البحث وإسقاطها على المؤسسة محل الدراسة مع استخدام القوائم المالية لو ا خلال الفترة ) 2010 – 2015 (، بالإضافة على المنهج الاحصائي ودراسة الحالة في الجانب التطبيقي. وقد توصّلت الدراسة إلى أنّ قياس وتقييم كفاءة إدارة التدفقات النقدية التشغيلية من خلال مؤشرات الكفاءة وأثرها على نسب السيولة والربحية لو دور أساسي في الكشف عن نقاط القوة والضعف للمؤسسة ، كما يساعد في اتخاذ الإجراءات التصحيحية المناسبة لتحسين كفاءتها ومن ثمّ الرفع من ربحيتها وتحسين سيولتها، كون نجاح المؤسسات الاقتصادية واستمرارها يتوقف على مدى قدرتها في تحقيق أعلى ربحية في ظل عالم تحتدم فيو المنافسة بالتوازي مع وضع مستوى مناسب من السيولة. كما خلصت الدراسة إلى وجود علاقة ذو دلالة إحصائية بين كفاءة التدفق النقدي التشغيلي والسيولة والربحية لمطاحن بلغيث خلال فترة الدراسة .